Foliar nutrient allocation patterns in Banksia attenuata and Banksia sessilis differing in growth rate and adaptation to low-phosphorus habitats. (3rd February 2021) - Han, Zhongming; Shi, Jianmin; Pang, Jiayin; Yan, Li; Finnegan, Patrick M; Lambers, Hans
Abstract: Background and Aims: Phosphorus (P) and nitrogen (N) are essential nutrients that frequently limit primary productivity in terrestrial ecosystems. Efficient use of these nutrients is important for plants growing in nutrient-poor environments. Plants generally reduce foliar P concentration in response to low soil P availability. We aimed to assess ecophysiological mechanisms and adaptive strategies for efficient use of P in Banksia attenuata (Proteaceae), naturally occurring on deep sand, and B. sessilis, occurring on shallow sand over laterite or limestone, by comparing the allocation of P among foliar P fractions. Methods: We carried out pot experiments with slow-growing B. attenuata, which resprouts after fire, and faster growing opportunistic B. sessilis, which is killed by fire, on substrates with different P availability using a randomized complete block design. We measured leaf P and N concentrations, photosynthesis, leaf mass per area, relative growth rate and P allocated to major biochemical fractions in B. attenuata and B. sessilis . Key Results: The two species had similarly low foliar total P concentrations, but distinct patterns of P allocation to P-containing fractions. The foliar total N concentration of B. sessilis was greater than that of B. attenuata on all substrates. The foliar total P and N concentrations in both species decreased with decreasing P availability. The relative growth rate of both species was positively correlated with concentrations of both foliar nucleic acid P and total N, but there was no correlation with other P fractions. Faster growing B. sessilis allocated more P to nucleic acids than B. attenuata did, but other fractions were similar. Conclusions: The nutrient allocation patterns in faster growing opportunistic B. sessilis and slower growing B. attenuata revealed different strategies in response to soil P availability which matched their contrasting growth strategy.